Trim33 masks a non-transcriptional function of E2f4 in replication fork progression - Rousseau, Vanessa; Einig, Elias; Jin, Chao; Horn, Julia; Riebold, Mathias; Poth, Tanja; Jarboui, Mohamed Ali; Flentje, Michael; Popov, Nikita (Nature Communications, 2023)
Replicative stress promotes genomic instability and tumorigenesis but also presents an effective therapeutic endpoint, rationalizing detailed analysis of pathways that control DNA replication. We show here that the transcription factor E2f4 recruits the DNA helicase Recql to facilitate progression of DNA replication forks upon drug- or oncogene-induced replicative stress. In unperturbed cells, the Trim33 ubiquitin ligase targets E2f4 for degradation, limiting its genomic binding and interactions with Recql. Replicative stress blunts Trim33-dependent ubiquitination of E2f4, which stimulates transient Recql recruitment to chromatin and facilitates recovery of DNA synthesis. In contrast, deletion of Trim33 induces chronic genome-wide recruitment of Recql and strongly accelerates DNA replication under stress, compromising checkpoint signaling and DNA repair. Depletion of Trim33 in Myc-overexpressing cells leads to accumulation of replication-associated DNA damage and delays Myc-driven tumorigenesis. We propose that the Trim33-E2f4-Recql axis controls progression of DNA replication forks along transcriptionally active chromatin to maintain genome integrity.